Associação entre o polimorfismo +3954 do gene da interleucina-1 beta, obesidade, LDL-oxidado e seu potencial efeito lipotóxico - Cattani, Maria Fernanda Manica Rizzi (2012)
Obesity is a systemic low grade inflammation, that is associated to the increased production of proinflammatory molecules by adipose tissue. Besides, the adiposity elevated induces cellular apoptosis and release of a large amounts of free fatty acids from disrupted adipocyte. These molecules tend to accumulate in the liver and other body tissues like skeletal muscles causing a phenomenon known as lipotoxicity. Evidence suggests that in addition to fatty acids there are other molecules that could have a severe effect lipotoxicity. This is the case of the inflammatory cytokine interleukin 1 beta (IL-1β). The IL-1β is a major inflammatory cytokines in immunity system. Studies suggest that its continued production may act by reducing the glucose influx, and induces the free radicals production contributing to the maintenance of a state of oxidative stress. For this reason, some authors have suggested that IL-1β would be a molecule glicolipotóxic. In humans the expression of IL-1B is under strong genetic control. The single nucleotide polymorphism (SNP) of C to T at nucleotide position +3953 of the IL-1B gene appears to be functional because it has been associated with increased production of IL-1β in vivo. Therefore, the aim of this study was to analyze the association between the polymorphism +3953 IL-1B gene with obesity, the influence on glycemic control, lipid and oxidized LDL molecule (oxLDL). For this, two studies were performed. The first was a case-control study with 880 Caucasian individuals, classified to obesity (non-obese = 283, overweight = 334, obese = 263), age between 18-92 years, and genotyped to IL-1B +3953 polymorphism. It was measured the bioanthropometric variables (DBP, SBP, IBM, height, weight, waist circumference) and serum parameters of blood glucose, lipid profile. In the second study, we included 225 subjects genotyped previously and measured the oxLDL serum levels, besides bioanthropometric and lipid profile measures. In both studies the volunteers did not smoke and had no cardiovascular disease or chronic degenerative diseases that could affect results. The IL-1B polymorphism genotypes were determined by PCR-RFLP and biochemical parameters by spectrophotometry. The first study results showed that the C allele (CC and CT) had a higher frequency in the group of obese and overweight when compared to the non obese group. The odds ratio showed 1.340 (95% CI: 1.119-1.605) times more chance of the obese group being CC carriers compared to non-obese group independent of gender and age. The second study showed that TT genotype carriers presented lower levels of oxLDL than patients with other genotypes. However no significant influence was observed of this polymorphism in blood glucose levels. Multivariate analysis showed that this result is independent of sex, age, obesity and hypertension. Thus, these results support the hypothesis that IL-1β is a molecule indeed obesogenic and lipotoxicity as previously suggested from animal models studies. Key-word: obesity. Interleukin-1beta. Oxidized-LDL